Исследование системы генерирования напряжения переменной частоты постоянной амплитуды на базе магнитоэлектрического генератора и полупроводникового преобразователя - Макаров, Д.В.; Харитонов, С.А.; Юхнин, М.М. (Технічна електродинаміка, 2012)
Electromagnetic processes in the power generating system of variable current and variable frequency based on permanent magnet synchronous machine and semiconductor converter carried out reactive load to influence equivalent flux linkage of generator on are studied. Relations to basic parameters of converter and generator be calculated are investigated.